The implementation guide to student learning supports in the classroom and schoolwide : new directions for addressing barriers to learning - Adelman, Howard S. 4 0 16; (Linda L.), Taylor, Linda; 5 (Thousand Oaks, California : Corwin Press, 2006)
Presents frameworks and practices designed to help schools and teachers create a comprehensive and adaptable system of learning supports designed to help students succeed.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Prevention.;Education;Prevention.;Education. -- School failure;Learning disabled children;School failure;Mentally handicapped children -- United States;United States.;United States; 20; 2